Simulated field study on the efficacy of the thermal application of a synergized pyrethroid formulation against Aedes aegypti (Linn.) and Culex quinquefasciatus say - Wan-Norafikah, Othman; Lee, Han Lim; Loke, Seau Rong; Andy-Tan, Wei Ann; Lau, Koon Weng; Sofian-Azirun, Mohd; Azidah, Abdul Aziz; Nor-Azlin, M.R.; Chen, Chee Dhang (Malaysian Society of Parasitology and Tropical Medicine, 2017)
Thermal application of a synergized pyrethroid formulation containing 0.8% w/w s-bioallethrin, 18.7% w/w permethrin and 16.8% w/w piperonyl butoxide was performed to evaluate its efficacy against adult and larva of Aedes aegypti and Culex quinquefasciatus. Three cages each containing 15 mosquitoes and paper cups each containing 25 larvae in 250 ml of water were deployed at each test point between 3 and 20 feet. The formulation was diluted (formulation:water) 1:33, 1:50 and 1:100, respectively, and applied using a thermal fogger. Sixty minutes post spraying, the adult knock down rate of Ae. aegypti and Cx. quinquefasciatus at a maximum distance of 15 feet using all dilution ratios ranged from 96.67 – 100% and 43.33 – 100%, respectively. More than 70.00% adult mortalities were recorded for both mosquito species at the distance between 3 feet and 15 feet 24 hours post spraying. In contrast, complete larval mortalities of Ae. aegypti were obtained at a maximum distance of 10 feet with dilution ratio of 1:33, while more than 80.00% larval mortalities were observed for Cx. quinquefasciatus at similar maximum distance using all dilution ratios. These results showed that thermal application using synergized pyrethroid formulation was effective against both mosquito species tested especially the adult stage.